Biologically grounded on-chip model identifies selective topographic reorganization within hyperexcitable corticostriatal networks - Maxime Poinsot; Marine Dos Santos; Baptiste Marthy; Ana Borges-Correia; Eduardo Gascon; Benoit Charlot; Maxime Cazorla (Proceedings of the National Academy of Sciences, 2026)
The mammalian cerebral cortex projects to the striatum in a precise, hierarchical topography, forming parallel loops that underlie sensorimotor, associative, and limbic processing. Despite the striatum’s lack of clear anatomical boundaries, these projections remain functionally segregated, suggesting the existence of intrinsic organizing principles. Disruptions in corticostriatal connectivity and excitability are common in neurodevelopmental disorders, but it remains unclear whether such abnormalities are a cause or a consequence of circuit dysfunction. Here, we hypothesized that the excitability state of cortical neurons plays a direct role in shaping the topographic organization of their striatal projections. To test this, we engineered a biologically faithful in vitro platform inspired by the Tesla valve, enabling adjacent corticostriatal territories to be modeled under controlled excitability regimes. We found that cortical hyperexcitability disrupted the normal developmental transition from axonal growth to stabilization, leading to premature invasion of neighboring territories and the formation of ectopic convergence zones. As a result, the segregation between parallel pathways was lost, while local connectivity patterns remained unaffected. These findings reveal that intrinsic, activity-sensitive mechanisms constrain long-range axonal growth to shape the wiring diagram of the corticostriatal projectome. They also highlight the power of biologically grounded on-chip models to uncover how early circuit vulnerabilities can lead to connectivity defects characteristic of disorders such as autism spectrum disorder, schizophrenia, epilepsy, and obsessive-compulsive disorder.